Systems approach to the design of commercial aircraft - Jackson, Scott; Moraes dos Santos, Ricardo (Boca Raton, FL : CRC Press, 2021)
"While aviation fatalities have thankfully fallen dramatically in recent years, the phenomena of complexity and cognitive bias have been shown to be factors in many accidents. An understanding of these phenomena promises to bring the fatality rate even lower, and a deeper understanding of commercial aircraft in the context of systems engineering will contribute to that trend. This book describes commercial aircraft from an advanced systems point of view, addressing complexity, cybersecurity, and systems architecting. In addition, it provides an explanation of systems engineering, describes how systems engineering forms a framework for commercial aircraft, covers how systems engineering and systems architecting relate to commercial aircraft, addresses complexity and shows how humans fit into systems engineering and the importance for commercial aircraft. It goes onto present how cybersecurity plays an important role in the mix and how human interface fits in. The readership includes designers of aircraft, manufacturers, researchers, systems engineers, and students"--
OCLC-licensed vendor bibliographic record.
Keywords: Aeronautics -- Systems engineering; Transport planes -- Design and construction; TECHNOLOGY / Manufacturing; TECHNOLOGY / Industrial Design / Product; TECHNOLOGY / Engineering / Mechanical